mRNA lipid nanoparticle cancer vaccine platform delivering multiple STING activators for enhanced antitumor activity - Ye Zeng; Junchao Xu; Jinjin Wang; Lulu Xue; Jiageng Liu; Hannah C. Geisler; Xu Ma; Jilian R. Melamed; Qiangqiang Shi; Marshall S. Padilla; Zhangyi Luo; Jingcheng Zhu; et al. (Proceedings of the National Academy of Sciences, 2026)
mRNA-based cancer vaccines offer a modular and safe platform to elicit antitumor immunity, yet their efficacy is often limited by inefficient mRNA delivery and inadequate dendritic cell (DC) activation, both of which are essential for initiating robust cytotoxic T cell responses. Inadequate innate immune activation coupled with poor antigen presentation further diminishes their effectiveness, particularly in immunologically “cold” tumors. While stimulator of interferon genes (STING) agonists can enhance DC maturation and cross-presentation, their therapeutic utility is constrained by poor intracellular delivery and limited colocalization with tumor antigens. In this study, we developed a lipid nanoparticle (LNP) platform via high-throughput screening of ionizable lipids for potent mRNA delivery to DCs both in vitro and in vivo. To amplify immune activation, we coencapsulated the STING agonists c-di-AMP (AMP) and manganese (Mn 2+ ) together with tumor antigen-encoding mRNA into the lead LNP formulation. This codelivery strategy synergistically activated type I interferon signaling, upregulated costimulatory molecules, enhanced antigen presentation, and elicited potent tumor-specific T cell responses and superior antitumor efficacy. Our results demonstrate that integrating innate immune stimulation with mRNA-LNP delivery provides a promising strategy to overcome current limitations in mRNA vaccine efficacy and to improve cancer immunotherapy outcomes.